Prevalence and factors associated with compassion fatigue among public health professionals - Samaniego, Bernadette; Michael Anthony Samaniego; Kristine Joy Ricafort-Acera (KHD-Production, 2025)
Compassion fatigue (CF) is a recognized occupational hazard among healthcare professionals, particularly in resource-constrained public health settings. This study aimed to determine the prevalence of CF and its associated factors among public health professionals in Aurora Province, Philippines. A descriptive, cross-sectional design was employed, using stratified random sampling with proportional allocation. Data were collected from 121 participants—including physicians, nurses, midwives, and medical technologists—through demographic and occupational questionnaires and the Professional Quality of Life Scale (ProQOL version 5). Results revealed high levels of compassion satisfaction (CS), low to average levels of burnout (BO), and average levels of secondary traumatic stress (STS), culminating in moderate levels of CF. At the same time, CS showed no significant correlation with CF (ρ = –0.114, p = 0.214), both BO (ρ = 0.856, p < .001) and STS (ρ = 0.892, p < .001) were strongly associated with CF. Job satisfaction emerged as a protective factor across all dimensions. These findings underscore the emotional resilience of public health professionals and highlight the need for targeted interventions addressing workload, rest, and job fulfillment. This study contributes context-specific evidence to inform the development of mental health strategies and policy for frontline healthcare workers in low-resource environments.